2012
DOI: 10.1017/s0263034612000882
|View full text |Cite
|
Sign up to set email alerts
|

Design of a high-efficiency dual-band coaxial relativistic backward wave oscillator with variable coupling impedance and phase velocity

Abstract: A dual-band high-efficiency coaxial relativistic backward wave oscillator (CRBWO) with asymmetric resonant reflector is designed and presented in this paper. Improved sectioned coaxial slow wave structure (SWS) with stepwise variation of coupling impedance and phase velocity is employed, and the performance of the dual-band CRBWO is investigated by use of a 2.5-D particle-in-cell (PIC) simulation code. When the diode voltage is 510 kV and beam current is 9.03 kA, an average microwave power of 1.0 GW with power… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Relativistic backward wave oscillator (RBWO) is one of the most promising high-power microwave (HPM) devices owing to its compact structure, high-conversion efficiency, and repetitive operation [1][2][3][4][5][6][7][8]. In the past several decades, many methods have been proposed to continuously improve the power capacity and pulse width of RBWOs, such as the overmoded structures, the more effective resonant reflector, and the surface treating methods [9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Relativistic backward wave oscillator (RBWO) is one of the most promising high-power microwave (HPM) devices owing to its compact structure, high-conversion efficiency, and repetitive operation [1][2][3][4][5][6][7][8]. In the past several decades, many methods have been proposed to continuously improve the power capacity and pulse width of RBWOs, such as the overmoded structures, the more effective resonant reflector, and the surface treating methods [9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Tang et al [15] have demonstrated an X-band dual-frequency coaxial relativistic backward wave oscillator (CRBWO) with sectioned SWSs and the frequencies of the two dominant frequencies were observed to be 10.06 and 10.49 GHz, respectively. Compared with MILO and other HPM devices, the RBWO has good adaptation to variable electron beam parameters [16]. Teng et al [6] designed a CRBWO with the experimental output frequency and power are 7.40 GHz and 710 MW, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, with the development of pulsed power technology Kuai et al, 2009;Liu et al, 2006;Yatsui et al, 2005;Zou et al, 2006), devices generating high power microwave (HPM) have been developed greatly (Benford et al, 2007;He et al, 2011;Li et al, 2010;Tang et al, 2013;Zhang et al, 2010). And power level in excess of 1 GW has been achieved in a number of cases (Cao et al, 2012a;Eltchaninov et al, 2003;Gao et al, 2012;Ge et al, 2010;Jin et al, 2011;Xiao et al, 2010).…”
Section: Introductionmentioning
confidence: 99%